Organic fertilizer application rates affect rhizosphere microbial communities and yield optimization in potato (Solanum tuberosum L. V7) - Han, Xiaodong; Yang, Jing; Li, Qi; Zhang, Lan; Li, Yuankai; Gai, Yaoyao; Sang, Yuying; Zhang, Ziyi (Frontiers in Microbiology, 2025)
BackgroundOrganic fertilizers enhance sustainable agriculture by providing nutrients and supporting microbial communities. However, optimal application rates that maximize potato yield while maintaining rhizosphere microbial diversity remain poorly understood.MethodsFour organic fertilizer levels (0, 40, 60, and 80% nitrogen replacement) were tested on potato rhizosphere bacterial and fungal communities across three growth stages using high-throughput 16S rDNA and ITS sequencing.ResultsBacterial richness increased progressively with organic fertilizer rates (80% > 60% > 40% > 0), with principal coordinate analysis revealing distinct community separations and largest differentiation during tuber expansion under 80% treatment. Bacterial and fungal communities were dominated by Proteobacteria, Acidobacteriota, and Gemmatimonadota, and Ascomycota, Mortierellomycota, and Basidiomycota, respectively. T60 maintained optimal balance of beneficial rhizospheric microorganisms and delivers superior yield outcomes compared with other fertilization regime. Potato yield responded quadratically to organic fertilizer application, with optimal yield of 81,020 kg/ha at 51.25% organic fertilizer rate, while bacterial and fungal diversity correlated with yield.ConclusionModerate organic fertilization (50–60% nitrogen replacement) optimizes both rhizosphere microbial diversity and potato productivity through enhanced nutrient cycling efficiency, providing a sustainable approach for potato production systems.